Genetic Parameters of Yield Character and Yield Components of Pigmented Rice Genotype Grown in Gogo - Amilia Qurota A’yun; I Gusti Putu Muliarta Aryana; I Wayan Sudika; Ni Wayan Sri Suliartini; M. Taufik Fauzi (Postgraduate, University of Mataram, 2024)
Increased public interest in red rice and black rice has triggered breeders to develop superior varieties that have high yields and are tolerant of the threat of drought. Genetic parameters are the basis needed for breeding to develop superior varieties. This research aims to examine the genetic parameters of pigmented rice genotypes grown upland. The experiment was carried out in June – September 2024 experimentally in the field using a gogo system, namely in Tampak Siring Village, Batukliang, Central Lombok, NTB. The design used was a Randomized Block Design (RAK) with 21 treatments, 10 red rice lines, 4 black rice lines, 4 parent lines, and 2 comparison varieties. Obtained 63 experimental units by repeating each treatment three times. The data collected was then analyzed using a one-way Analysis of Variance (ANOVA) test with a Randomized Block Design (RAK) model at a confidence level of 95% (α=5%), genetic diversity coefficient (KKG) formula, heritability and genotypic correlation. Referring to the analysis that has been carried out, the findings of the coefficient of genetic diversity and heritability of the number of full grains, weight of 100 grains, yield per plot of red rice and black rice lines are in the high category. The number of productive tillers, weight of 100 grains and weight of grain per hill had a significant positive correlation with the yield per plot, while the number of empty grain parameters had a significant negative correlation with the yield per plot.